2010
DOI: 10.1248/bpb.33.53
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression of BCL2/Adenovirus EIB 19-kDa-Interacting Protein 3 mRNA, a Candidate for Intrinsic Depression-Related Factor, and Effects of Imipramine in the Frontal Cortex of Stressed Mice

Abstract: We previously reported that long-term treatment with some antidepressants at low concentrations upregulates BCL2/adenovirus E1B 19-kDa-interacting protein 3 (BNIP3) mRNA expression in NG108-15 cells without causing cell damage, suggesting that BNIP3 is a candidate of intrinsic depressive disorder-related factor(s). In this study, to clarify the physiologic functions of BNIP3, we investigated whether BNIP3 is actually related to the depressive condition in the brain using learned helplessness (LH) mice, an anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Among targets that have been experimentally validated ( Table 2 ) and that are co-expressed in prefrontal cortex, at least three (VEGFA, BCL2, and DNA methyltransferase 3B) have been previously implicated in depression or suicide [51], [52], [53]. Of miRNAs that showed the largest and most robust changes in depressed subjects, predicted targets included several brain-active transcription factors such as MITF, SMAD5, MYCN, estrogen receptor alpha (ESR1) and BACH2.…”
Section: Discussionmentioning
confidence: 99%
“…Among targets that have been experimentally validated ( Table 2 ) and that are co-expressed in prefrontal cortex, at least three (VEGFA, BCL2, and DNA methyltransferase 3B) have been previously implicated in depression or suicide [51], [52], [53]. Of miRNAs that showed the largest and most robust changes in depressed subjects, predicted targets included several brain-active transcription factors such as MITF, SMAD5, MYCN, estrogen receptor alpha (ESR1) and BACH2.…”
Section: Discussionmentioning
confidence: 99%
“…Desipramine, a typical antidepressant, improved the index of depression. We previously reported the similar effect of imipramine [9], whereas the index became worse in water-administered animals with depression. These results suggest that this strategy is highly useful to evaluate the drug effect using the minimal number of animals.…”
Section: Discussionmentioning
confidence: 70%
“…The paradigm and experimental conditions used to induce LH behavior in mice are the same as previously reported [9]. In the avoidance test conducted on day 4, mice were selected for the experiments as LH animals if escape failed more than 10 times.…”
Section: Methodsmentioning
confidence: 99%
“…It has interestingly been suggested that mammalian BNIP3 protein can be a candidate for an intrinsic antidepressive effect-related factor and an antistress reaction factor [ 88 , 89 ]. Enhanced Bnip3 expression in NG108-15 cells, which possess the serotonin 2C receptor (5-HT2CR) mRNA system, was observed after exposure to Hochu-ekki-to (HET), a (Wakan-yaku) Sino-Japanese traditional drug with antidepressive effects, as well as after exposure to typical antidepressants [ 88 ].…”
Section: Discussionmentioning
confidence: 99%